Facile fabrication of luminescent organic dots by thermolysis of citric acid in urea melt, and their use for cell staining and polyelectrolyte microcapsule labelling - Zholobak, Nadezhda M.; Popov, Anton L.; Shcherbakov, Alexander B.; Popova, Nelly R.; Guzyk, Mykhailo M.; Antonovich, Valeriy P.; Yegorova, Alla V.; Scrypynets, Yuliya V.; Leonenko, Inna I.; Baranchikov, Alexander Ye.; Ivanov, Vladimir K. (Beilstein Journal of Nanotechnology, 2016)
Luminescent organic dots (O-dots) were synthesized via a one-pot, solvent-free thermolysis of citric acid in urea melt. The influence of the ratio of the precursors and the duration of the process on the properties of the O-dots was established and a mechanism of their formation was hypothesized. The multicolour luminescence tunability and toxicity of synthesized O-dots were extensively studied. The possible applications of O-dots for alive/fixed cell staining and labelling of layer-by-layer polyelectrolyte microcapsules were evaluated.
Keywords: cell culture; citric acid; layer-by-layer (LbL)-microcapsules; luminescence; organic dots (O-dots); staining; toxicity